The sodium-glucose cotransporter-2 inhibitor canagliflozin alleviates endothelial dysfunction in a rat bypass model - Ma, Ming; Lian, Shuo; Kraft, Patricia; Mayer, Tobias; Sayour, Alex Ali; Karck, Matthias; Szabó, Gábor; Korkmaz-İçöz, Sevil (Biochemical pharmacology, 2026)
Ischemia/reperfusion (IR) injury during coronary artery bypass grafting surgery has detrimental impacts on endothelial integrity and function. Studies have suggested that canagliflozin (CANA) mitigates the risk of cardiovascular events, independently of diabetes. We hypothesized that the supplementation and/or administration of CANA protects vascular grafts in a bypass model in non-diabetic Lewis rats. The aortic arches of control rats (n = 9) were harvested, aortic rings were prepared, then mounted in organ baths. In the IR and IR + CANAsuppl groups (n = 8/group), aortic arches were preserved in either saline or CANA-supplemented saline (5 µM) for 1 h at 4 °C before transplantation. In the IR + CANAinject and IR + CANAsuppl+inject groups (n = 9/group), aortic arches were preserved in cold saline or CANA for 1 h and recipients received CANA (10 µg/kg, intravenous) 5 min prior to reperfusion. After 1 h of in vivo blood reperfusion, ex vivo vascular function was assessed and immunohistochemistry was performed. The decreased maximum relaxation (Rmax) to acetylcholine in the IR group compared to controls (20 ± 3 % vs 83 ± 2 %, p < 0.05) was improved in both the IR + CANAinject (36 ± 2 % vs. 20 ± 3 %, p < 0.05) and IR + CANAsuppl+inject (45 ± 3 % vs. 20 ± 3 %, p < 0.05) groups. Additionally, the IR + CANAsuppl+inject rings exhibited a further increased Rmax to acetylcholine compared to both the IR + CANAsuppl (45 ± 3 % vs. 31 ± 2 %, p < 0.05) and IR + CANAinject (45 ± 3 % vs. 36 ± 2 %, p < 0.05) groups. Increased DNA strand breaks in the IR group compared to controls were decreased in all CANA groups. The reduced immunoreactivity of CD-31 was ameliorated in the IR + CANAinject and IR + CANAsuppl+inject groups. CANA alleviates endothelial dysfunction induced by IR injury in a rodent model of revascularization.
Online verfügbar: 4. Dezember 2025, Artikelversion: 8. Dezember 2025
Gesehen am 10.02.2026